THE ROLE of PRODUCT CHARACTERISTICS and PRICE DISCOUNTS in ENHANCING CUSTOMER SATISFACTION and LOYALTY - Abnur, Asman; Edy wibowo, Agung; Syaiful, Hendra; Christian Lumban Tobing, Vargo; Wasiman, Wasiman; Nyoman Budhiartha, I (Universitas Putera Batam, 2025)
This study aims to examine the role of product characteristics and price discounts in building customer satisfaction and loyalty. The study is motivated by the growing competition among café businesses, where customer retention and satisfaction are crucial for business sustainability. This research explores whether product features and price discounts can effectively shape customer loyalty, either directly or through the mediating role of customer satisfaction. Using a quantitative approach, data were collected through purposive sampling involving 114 respondent who had previously visited MoMoo Café, located in a popular culinary tourism area. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results show that price discounts do not have a direct and significant effect on customer loyalty. However, discounts were found to significantly influence customer satisfaction, which in turn significantly affects customer loyalty. This indicates that although discounts do not directly create loyal customers, they enhance satisfaction through the perception of value received, which subsequently drives loyalty. In contrast, product characteristics were found to have no significant influence, either directly on loyalty or on customer satisfaction. These findings highlight the importance of customer satisfaction as a strategic mediator in the formation of loyalty. Therefore, businesses operating in tourist areas should not rely solely on price promotions but should focus on creating a satisfying customer experience. Enhancing service quality, ambiance, and emotional engagement with the brand can result in more sustainable loyalty than price-based incentives alone. This study contributes to the consumer behavior literature in the tourism context by emphasizing the indirect role of price discounts and the central position of satisfaction in building long-term customer relationships.